KONSEPSI ZAKAT ONLINE PERSPEKTIF MASLAHAH WAHBAH AZ ZUHAILY - Moh Subhan (ASASI: Journal of Islamic Family Law, 2021)
Zakat is one of the pillars of Islam in the form of maliyah ijtima'iyah worship that must be fulfilled for every Muslim who is able to comply with the criteria in Islamic law. Zakat has two dimensions, namely the vertical and horizontal dimensions. In the dimension of zakat as a form of worship and real evidence of obedience to Allah as his god and a sign of gratitude for blessings, the horizontal dimension of zakat as an embodiment of a sense of justice, love and empathy from groups who are able to effectively treat the less fortunate. In this context, zakat is expected to realize equity and social justice between fellow human beings and minimize social and economic problems of the people. The development of science and technology in various ways has brought significant changes to the lifestyle and culture of the community, including fulfilling the obligation of zakat. In the current digital era, there is a tendency for some people to fulfill their zakat obligations online through sites or applications that have been provided by zakat institutions, because they are considered more practical and maslahah to the community and can ease and facilitate the community in performing zakat obligation services.